A methodology for precise estimation of rain attenuation on terrestrial millimetre wave links from raindrop size distribution measurements - Manhal Alhilali; Mustafa Ghanim; Jafri Din; Hong Yin Lam (Universitas Ahmad Dahlan, 2019)
Attenuation by atmospheric rain is the most significant impairment in millimetre wave frequencies (mmWave). Modern instruments could provide detailed measurements of rain, such as raindrop size distributions (DSDs). The analysis of DSDs could estimate their effects on past or co-located links measurements. This study presents propagation analysis in the mmWave bands using measurements of two terrestrial links working at 26 and 38 GHz carried out in Johor, Malaysia. Statistics obtained have been analysed in detail to extract any excess attenuation. The DSDs provided by a disdrometer have been used to estimate rain attenuation. The derived results show that the estimation can provide reasonable accuracy after extracting the wet antenna effects and having the advantage of the availability of measurements from various types of equipment.